Phenomenological Study: Spiritual Needs of Cancer Patients at Dr. Mohammad Hoesin General Hospital, Palembang - Kurianto, Endar; Evi Yuni Mistati; Kuniarti Rachmat; Ulya Syafitri M (RSUP Dr Moh Hoesin Palembang, 2023)
Phenomenological Study: Spiritual Needs of Cancer Patients at Dr. Mohammad Hoesin General Hospital, Palembang. Cancer is the main cause of death in the world. Cancer does not only cause problems physically, but also psychologically, socially and spiritually. In holistic care, not only focusing on physical care alone, psychological, social and spiritual care is also very important. Fulfillment of spiritual needs that are not optimal causes a decrease in the quality of care and quality of life for patients. This study aims to explore in depth the phenomenology of the spiritual needs of cancer patients at Dr Mohammad Hoesin General Hospital, Palembang. The research method uses a qualitative phenomenological approach. The research sample consisted of ten cancer patient respondents using purposive sampling. Data was collected using in-depth interviews from October to December 2022. All respondents were women, aged 25-51 years. There are four main themes, 1) acceptance responses to illness experienced and during illness, 2) changes in aspects of life experienced during illness, 3) obstacles to worship during illness and 4) hope for the future in living life. The spiritual aspect is an important aspect that needs attention, especially in the care of cancer patients in hospitals.